2009
DOI: 10.5194/bg-6-2637-2009
|View full text |Cite
|
Sign up to set email alerts
|

Strain-specific responses of <i>Emiliania huxleyi</i> to changing seawater carbonate chemistry

Abstract: Abstract. Four strains of the coccolithophore E. huxleyi (RCC1212, RCC1216, RCC1238, RCC1256) were grown in dilute batch culture at four CO 2 levels ranging from ∼200 µatm to ∼1200 µatm. Growth rate, particulate organic carbon content, and particulate inorganic carbon content were measured, and organic and inorganic carbon production calculated. The four strains did not show a uniform response to carbonate chemistry changes in any of the analysed parameters and none of the four strains displayed a response pat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

40
385
8
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 372 publications
(434 citation statements)
references
References 33 publications
40
385
8
1
Order By: Relevance
“…These results are in contrast with those of earlier studies examining the combined effects of elevated pCO 2 and temperature: one study found decreased PIC content in the same strain (CCMP371) [23], and two studies found no change in PIC content in different strains (RCC1228 and PML B92/11) [18,22] (table 6). Responses of calcification to elevated pCO 2 are known to vary across strains of E. huxleyi [7,8,15], and responses to the combination of elevated pCO 2 and temperature could also be strain-specific. Therefore, a strain-specific response could explain some of the different results in the experiments under elevated pCO 2 and temperature, but not the different response of the same strain (CCMP 371) [7,8,23].…”
Section: Discussion (A) Inorganic Carbon Physiologymentioning
confidence: 99%
See 2 more Smart Citations
“…These results are in contrast with those of earlier studies examining the combined effects of elevated pCO 2 and temperature: one study found decreased PIC content in the same strain (CCMP371) [23], and two studies found no change in PIC content in different strains (RCC1228 and PML B92/11) [18,22] (table 6). Responses of calcification to elevated pCO 2 are known to vary across strains of E. huxleyi [7,8,15], and responses to the combination of elevated pCO 2 and temperature could also be strain-specific. Therefore, a strain-specific response could explain some of the different results in the experiments under elevated pCO 2 and temperature, but not the different response of the same strain (CCMP 371) [7,8,23].…”
Section: Discussion (A) Inorganic Carbon Physiologymentioning
confidence: 99%
“…One of the first studies on E. huxleyi revealed decreasing calcification rates under elevated pCO 2 [5]. While this response was later observed in a number of other studies [9][10][11][12][13][14][15], contrasting results have also been reported where elevated pCO 2 resulted in either no change in calcification (where in this case the term 'calcification' refers to calcium carbon quota and/or calcification rate) [15] or increased calcification [4]. Regardless of outcome, these earlier studies tested the response of E. huxleyi to elevated pCO 2 in short-term experiments (less than 20 generations).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The balance of these two roles has considerable ramifications for the global carbon cycle. The expected response of calcifying plankton to ocean acidification is presently unclear, with culture studies producing conflicting responses of coccolithophores to increasing levels of CO 2 (Riebesell et al 2000;IglesiasRodriguez et al 2008;Langer et al 2009). An ability to accurately characterize naturally occurring coccolithophore populations is essential for assessing their response to ocean acidification over time.…”
mentioning
confidence: 99%
“…In this context a series of laboratory studies with monocultures of calcifying coccolithophores were conducted to investigate responses in calcification to variations in carbonate chemistry, often with Emiliania huxleyi, (e.g. Zondervan et al, 2002;Iglesias-Rodriguez et al, 2008;Langer et al, 2009;Barcelos e Ramos et al, 2010). These studies were motivated by the expectation that the observed trend in ocean acidification (OA) will affect calcifying algae and that their physiology is likely sensitive to the seawater's calcite saturation state (Feely et al, 2004;Orr et al, 2005).…”
Section: Introductionmentioning
confidence: 99%